The "Rose System" in Overcoming the Second Cholera Outbreak in Jakarta from May 25-30, 1976 - Adnan S. Wiharta; R. Sutejo (Paediatrica Indonesiana, 1978)
1.a. During a short cholena outbreak in Jakarta frnom 25th May to 30th May, 1976, 70 children aged from 6 months to 13 years suffering from acute diarrhoea and dehydration, shock or pre-shock were admitted to the provisional Rehydnation Cetntre in the outpatient section of the Departmernt of Child Heatth, University of Indonesia/Dr. Cipto Mangunkusumo General Hospital, Jakarta.b. None died.c. 71.9% of the stool specimens from 32 patients revealed Vibrio Cholera El Tor Ogawa type.2. The methodology used was the so-called "ROSE" system :a. Rehydration with ringer's lactate solution.b. Oralyte in boiled water given ad libiÂ·tum.c. Oralyte solution and intravenous solution given Simultaneously.d. Education to the parents on the importance of giving oralyte solution ad libitum.3. This paper dealt with the second success of the Rose system in facing a cholera outbreak.